MITRAL VALVE PARAMETERS ของลิ้นหัวใจไมตรัลที่วัดจากข้อมูลคลื่นเสียงความถี่สะท้อนหัวใจผ่านทางเดินอาหารสามมิติ: ความสัมพันธ์ของค่าที่ได้จากโปรแกรมคิวแลปและโปรแกรมทอมเทค - รณพิชัย โชคสุวัฒนสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
Background: 3-Dimensional Transesophageal echocardiogram (3D TEE) has been a standard method to evaluate the structural and functional features of mitral valve. Subsequently, the mitral valve parameters from 3D TEE can be reconstructed and analyzed by different software. So far, there are no comparative studies among data derived from different types of software analysis. In this study, we compare mitral valve parameters and analysis time derived from vendor-specific Qlab® software and vendor-neutral TomTec® software. Method: Twenty-five consecutive patients (mean age = 56 years) were registered at an echocardiography laboratory, the King Chulalongkorn Memorial Hospital, between July 2014 to January 2015. TEE dataset were acquired with Philips system (iE33 or EPIQ 7C, X7-2t probe). Mitral valve data were analyzed by Qlab® software ver 4.2 and TomTec® software ver. 2.0 separately. Statistical analyses were Pearson correlation and paired t-test study. Bland-Altman plot was used to evaluate the agreement between the same parameter from Qlab® and TomTec®. Results: Most of mitral valve parameters, included anterior mitral leaflets area, posterior mitral leaflets area, mitral annular AP diameter and mitral annular AL-PM diameter, demonstrated good correlation between two software (r>0.7), however aortic-mitral angle parameter exhibited only moderate correlation (r = 0.6). Intra-rater variability (Reliability) showed a good correlation between the first and the second measurement in both software systems. Analysis time was remarkably shorter with TomTec® software (34 ± 9 seconds) compared to Qlab® software (120 ± 22 seconds), p valve = 0.026. Conclusion: 3D-TEE Mitral Valve Parameters derived from both software systems were strongly correlated. The TomTec® software has the advantage of shorter analysis time and is vendor-neutral. However, the cost and additional special hardware setup are the disadvantage TomTec® software.